2010
DOI: 10.1186/1471-2407-10-126
|View full text |Cite
|
Sign up to set email alerts
|

The RNA binding protein HuR differentially regulates unique subsets of mRNAs in estrogen receptor negative and estrogen receptor positive breast cancer

Abstract: BackgroundThe discordance between steady-state levels of mRNAs and protein has been attributed to posttranscriptional control mechanisms affecting mRNA stability and translation. Traditional methods of genome wide microarray analysis, profiling steady-state levels of mRNA, may miss important mRNA targets owing to significant posttranscriptional gene regulation by RNA binding proteins (RBPs).MethodsThe ribonomic approach, utilizing RNA immunoprecipitation hybridized to microarray (RIP-Chip), provides global ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 75 publications
3
54
0
3
Order By: Relevance
“…Additionally, the data obtained with our conditional knockout mouse model suggest that HuR-dependent and -independent control mechanisms of GATA-3 and Th2 cytokines may coexist. Consistent with this idea, we have recently demonstrated that HuR can positively or negatively control expression of the same genes in breast cancer cells depending on the cellular milieu (59,60).…”
Section: Discussionsupporting
confidence: 57%
“…Additionally, the data obtained with our conditional knockout mouse model suggest that HuR-dependent and -independent control mechanisms of GATA-3 and Th2 cytokines may coexist. Consistent with this idea, we have recently demonstrated that HuR can positively or negatively control expression of the same genes in breast cancer cells depending on the cellular milieu (59,60).…”
Section: Discussionsupporting
confidence: 57%
“…The discrepancies here could partly be due to different time-points used in the microarray and proteomics analyses, 24 h and 48 h, respectively. Furthermore, the steady-state-levels of mRNA and protein rarely correlate directly because of complicated post-transcriptional control mechanisms (12,13). Although proteomic strategies are currently limited to the identification of only a fraction of the cell's proteome, they complement the microarray experiments as they offer a read-out of the functional component of the transcript activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our work involving targets discovered by RIP-Chip in cell lines under normoxic conditions indicates that HuR may indeed regulate the same targets in opposite fashion, dependent upon cellular milieu, though the reasons are not presently clear. 42 There are obvious differences when performing these experiments under the hypoxic conditions which operate in animals in which tumors form. The published data has both indicated that HuR overexpression correlates with increased as well as decreased aggressiveness in breast cancer.…”
Section: Methodsmentioning
confidence: 99%